PERSEPSI MASYARAKAT TERHADAP PERUBAHAN DESA MENJADI KAMPUNG ADAT (DESA ADAT) DI DESA KUALA GASIB KECAMATAN KOTO GASIB KABUPATEN SIAK - lasmaria, Juliwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted from the change of the village name into a traditional village earlier has been used in the village of Kuala Gasib Koto Gasib Siak District. The formulation of the study was "How was the public perception about the village changed into a traditional village in Kuala Gasib Koto Gasib Siak District. This study was aimed to determine how was the public perception about the village changed into a traditional village in Kuala Gasib Koto Gasib Siak District. This research was conducted in the village of Kuala Gasib Koto Gasib Siak District, in November 2015. This research was a qualitative descriptive with population were the entire population in the village of Kuala Gasib Koto Gasib Siak District, where the sample in this study was based on "purposive sampling" and the sample was the entire staffs of the village and adat communities. Then the data from the calculation of the percentage obtained 85.2% of respondents stated strongly agree and 0.1% did not agree. Thus, the public perception about the village changed into kampung adat (traditional village) in the village of Kuala Gasib Koto Gasib Siak District was in very good category.Keywords: Perception , The village changed into a traditional village